Combination of DKK1 and AFP improves diagnostic accuracy of hepatocellular carcinoma compared with either marker alone - Erdal, Harun; Utku, Özlem Gül; Karatay, Eylem; Çelik, Bülent; Elbeg, Şehri; Doğan, İbrahim (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: The Wnt/ß-catenin pathway plays a prominent role in hepatocellular carcinoma (HCC). The Dickkopf (DKK) proteins (DKK1-4) are known Wnt antagonists; the overexpression of DKK1 has been demonstrated in HCC, and increased DKK3 methylation in the HCC tissue is associated with worse prognosis. Thus, the aim of our study was to demonstrate the diagnostic accuracy of serum DKK1 and DKK3 in HCC in comparison with that of serum alpha-fetoprotein (AFP). Materials and Methods: We included consecutive 40 HCC patients, 54 cirrhosis patients, and 39 healthy controls. Serum DKK1 and DKK3 levels were measured by an enzyme-linked immunosorbent assay, and serum AFP levels were measured by a chemiluminescence assay. Results: The AFP levels differed in each group and could help differentiate between groups (p<0.001). The DKK1 levels could help differentiate the HCC group from cirrhosis and control groups (p<0.001), and the DKK3 levels could help differentiate HCC and cirrhosis groups from the control group (p<0.001). Combined usage of DKK1 and AFP increased the diagnostic yield, with a sensitivity, specificity, positive predictive value, and negative predictive value of 87.5%, 92.3%, 92.1%, and 87.8%, respectively. Conclusion: Although AFP is superior to DKK1 and DKK3 in the diagnosis of HCC, the combination of DKK1 and AFP showed a better diagnostic yield than AFP alone.